2004
DOI: 10.1079/phn2004613
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a semi-quantitative food-frequency questionnaire used among 2-year-old Norwegian children

Abstract: Objectives: An adequate diet is of profound importance in infancy and early childhood. To ensure an optimal diet, knowledge about actual intake must be obtained. The aims of this study were to assess the validity of a semi-quantitative food-frequency questionnaire (SFFQ) applied in a large nation-wide survey among 2-year-old children and to examine the validity of the SFFQ in relation to different background parameters. Design: The SFFQ was administered to the parents close to the child's second birthday, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
130
6
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(163 citation statements)
references
References 10 publications
26
130
6
1
Order By: Relevance
“…The correlations are also similar to the results found by Blum et al (1999) among 129 children aged 1-2 y. The agreement across quartiles between the two methods obtained in our study was on average (median) 38%, which is comparable to what we have observed among adolescents and adults (Nes et al, 1992;Andersen et al, 1995Andersen et al, , 1999. When using classification into quartiles, one will expect by chance to get 25% into the same quartile and 12.5% in the opposite quartiles.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The correlations are also similar to the results found by Blum et al (1999) among 129 children aged 1-2 y. The agreement across quartiles between the two methods obtained in our study was on average (median) 38%, which is comparable to what we have observed among adolescents and adults (Nes et al, 1992;Andersen et al, 1995Andersen et al, , 1999. When using classification into quartiles, one will expect by chance to get 25% into the same quartile and 12.5% in the opposite quartiles.…”
Section: Discussionsupporting
confidence: 92%
“…In these validation studies weighed records were also used as the reference method (7-14 days). We observed average correlation coefficients for nutrients of 0.52 among 18-y-old Norwegian adolescents (Andersen et al, 1995), and correlation coefficients of 0.59 and 0.51 among elderly women and a group of men, respectively (Nes et al, 1992;Andersen et al, 1999). The correlations are also similar to the results found by Blum et al (1999) among 129 children aged 1-2 y.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Physical activity in this context was defined as activity causing the subject to perspire and experience shortness of breath. Food and nutrient intake were estimated by a standardized quantitative food frequency questionnaire (28), and calculations were performed with use of the Norwegian Food Composition Table (29). Physical disability was measured by the Childhood Health Assessment Questionnaire (C-HAQ) and, for patients older than age 18 years, by the HAQ (30,31).…”
Section: Methodsmentioning
confidence: 99%
“…A previous investigation using data from this cohort suggested that the dietary questionnaire may have resulted in the under-reporting of dietary energy intake. 11 Other studies have conversely noted an over-reporting of energy intake, 22,23 suggesting that results concerning dietary intake should be viewed with caution. Further, it is likely that crosssectional measures of dietary intake would not be the most appropriate when investigating metabolic factors in an overweight or obese population.…”
Section: Discussionmentioning
confidence: 99%